Hubungan Pengetahuan Ibu Tentang â€œIsi Piringkuâ€ dengan Kejadian Stunting Anak Balita Usia 12-59 Bulan - Devriany, Ade; Wulandari, Diah Ayu (Politeknik Kesehatan Tanjung Karang, 2021)
A toddler is an age group that is prone to nutrition and disease. The handling of stunting in the Bangka Belitung Islands Province is a priority in Bangka Regency. Mendo Village has the highest percentage of stunting, which is 17,7%. The purpose of this study is to analyze the relationship mother's knowledge about Isi Piringku with the nutritional status of children aged 12-59 months in Mendo Village, Mendo Barat Subdistrict. The design of this study was a cross-sectional study which was conducted in Mendo Village, Mendo Barat Subdistrict. The number of samples used was 96 mothers and toddlers aged 12-59 months Data analysis used univariate and bivariate analysis with chi-square statistical tests. The results of this study are More toddler mothers have good knowledge about Isi Piringku is 64,6% (62 people), while the nutritional status of stunting toddlers is 6% (6 people). There is no correlation between mother's knowledge about Isi Piringku with the nutritional status of children age 12-59 months in Mendo Village, Mendo Barat Subdistrict with a p-value=0,125 (p-value>0,05). This happens because the respondent has toddlers with normal nutritional status but the respondent has less knowledge about Isi Piringku, and vice versa being influenced by economic factors/work, education, age, and environment.